Nest predation, food, and female age explain seasonal declines in clutch size - Decker, Karie L.; Conway, Courtney J.; Fontaine, Joseph J. (Evolutionary ecology, 2012)
The selection pressures responsible for intra- and interspecific variation in avian clutch size have been debated for over half a century. Seasonal declines in clutch size represent one of the most robust patterns in avian systems, yet despite extensive research on the subject, the mechanisms underlying this pattern remain largely unknown. We tested a combination of experimental and observational predictions to evaluate ten hypotheses, representing both evolutionary and proximate mechanisms proposed to explain seasonal declines in avian clutch size. In line with long held life-history theory, we found strong support for both an evolved and proximate response to food availability for young. We also found evidence consistent with predictions that proximate level experiential nest predation influences seasonal declines in clutch size. Finally, older females appear to invest more in reproduction (initiate nests earlier and lay larger clutches) and choose better territories than younger females. Our results highlight the importance of examining multiple hypotheses in a theoretical context to elucidate the ecological processes underlying commonly observed patterns in life history.